Біохімічні показники сироватки крові і сперми у хворих на хронічний простатит після комплексного патогенетичного лікування = Biochemical indicators of blood serum and sperm patients with chronic prostatitis after complex pathogenetic treatment - Shuhtin, V. V.; Sknar, V. N.; Shuhtina, I. N.; Zukow, W. (Journal of Education, Health and Sport, 2015)
Shuhtin V. V., Sknar V. N., Shuhtina I. N., Zukow W. Біохімічні показники сироватки крові і сперми у хворих на хронічний простатит після комплексного патогенетичного лікування = Biochemical indicators of blood serum and sperm patients with chronic prostatitis after complex pathogenetic treatment. Journal of Education, Health and Sport. 2015;5(12):608-613. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.44648 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A608-613 http://pbn.nauka.gov.pl/works/693566 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.12.2015. Revised 15.12.2015. Accepted: 29.12.2015. УДК 616.699:616.697-07:616.69-008.8-097 БІОХІМІЧНІ ПОКАЗНИКИ СИРОВАТКИ КРОВІ І СПЕРМИ У ХВОРИХ НА ХРОНІЧНИЙ ПРОСТАТИТ ПІСЛЯ КОМПЛЕКСНОГО ПАТОГЕНЕТИЧНОГО ЛІКУВАННЯ Biochemical indicators of blood serum and SPERM patients with chronic prostatitis After complex pathogenetic treatment В. В. Шухтін¹, В. М. Скнарь², І. М. Шухтіна2, В. А. Жуков3 V. V. Shuhtin, V. N. Sknar, I. N. Shuhtina, W. Zukow ¹ ДП «Український науково-дослідний інститут медицини транспорту» ² Одеський національний медичний університет ² Uniwersytet Kazimierza Wielkiego, Bydgoszcz 1SE "Ukrainian Scientific Research Institute of Transport Medicine, Ministry of Health of Ukraine", Odessa 2Odessa National Medical University, Odessa 3Kazimierz Wielki University, Bydgoszcz Abstract In patients with chronic prostatitis were determined in serum malondialdehyde content and total proteolytic activity (OPA), which serves as a marker of inflammation, as well as the activity of catalase. Sperm concentration was determined protein content and the lysozyme ASO. Inclusion in the complex therapeutic agents medications prebiotics (Inu-lin + Exo) and immunomodulators has increased the effectiveness of treatment (reduction of the concentration of protein in the sperm and the ASO) due to increased content of lysozyme. Keywords: prostate, serum, semen, biochemical parameters, prebiotics. Реферат БИОХИМИЧЕСКИЕ ПОКАЗАТЕЛИ СЫВОРОТКИ КРОВИ И СПЕРМЫ БОЛЬНЫХ ХРОНИЧЕСКИМ ПРОСТАТИТОМ ПОСЛЕ КОМПЛЕКСНОГО ПАТОГЕНЕТИЧЕСКОГО ЛЕЧЕНИЯ. У больных хроническим простатитом определяли в сыворотке крови содержание малонового диальдегида и общую протеолитическую активность (ОПА), которые служили маркерами воспаления, а также активность каталазы. В сперме определяли концентрацию белка, ОПА и содержание лизоцима. Включение в комплекс лечебных средств препаратов пребиотиков (инулин + ЭКСО) и иммуномодуляторов повысило эффективность лечения (снижение концентрации белка и ОПА в сперме) за счет увеличения содержания лизоцима. Ключевые слова: простатит, сыворотка крови, сперма, биохимические показатели, пребиотики.